Space-based GAMMA-400 mission for direct gamma- and cosmic-ray observations. (February 2019) - Topchiev, N P; Galper, A M; Arkhangelskaja, I V; Arkhangelskiy, A I; Bakaldin, A V; Chernysheva, I V; Dalkarov, O D; Egorov, A E; Gusakov, Yu V; Kheymits, M D; Leonov, A A; Yu Naumov, P; et al.
Abstract: The future space-based GAMMA-400 mission is intended for direct gamma- and cosmic-ray observations in the highly elliptic orbit during 7-10 years. GAMMA-400, currently developing gamma-ray telescope, will observe in the energy range from ∼20 MeV to several TeV some regions of the Universe (such as Galactic Center, Fermi Bubbles, Crab, Cygnus, etc.) with the unprecedented angular (∼0.01° at Eγ = 100 GeV) and energy (∼1% at Eγ = 100 GeV) resolutions better than the Fermi-LAT, as well as ground gamma-ray telescopes, by a factor of 5-10. GAMMA-400 will also study cosmic rays in the energy range of up to ∼20 TeV due to deep calorimeter (22 r.l. and 53 r.l. for vertical and lateral events, respectively). GAMMA-400 will permit to resolve gamma rays from dark matter particles, identify many discrete sources (many of which are variable), to clarify the structure of extended sources, to specify the data on the diffuse emission. GAMMA-400 will also specify the sources and the spectra of cosmic-ray electrons + positrons.